EFFECT OF BIO FERTILIZERS AND CHEMICALS ON VEGETATIVE GROWTH AND YIELD OF GERBERA - P. NEELIMA , ALKA SINGH; T. SUMATHI (The Bioscan, 2018)
An investigation was carried out to study the effect of bio fertilizers (Azotobacter @ 1l/ha and VAM @ 2g/plant) as soil application, chemicals (25 and 50 ppm each of spermine and salicylic acid) and organic growth substances (0.5 and 1% banana pseudo stem sap and 4% vermiwash) as foliar spray on gerbera under NV polyhouse condition. Gerbera plants inoculated with bio fertilizers showed improved growth and yield attributes over uninoculated plants. Among the foliar spray treatments, 25 ppm spermine and 4% vermiwash significantly increased plant height, plant spread, number of leaves, chlorophyll content in the leaf, MSI in the petal tissue, lignin content in the stalk, yield and vase life of gerbera. Treatment combination of bio fertilizer inoculation (Azo and VAM) along with 25 ppm spermine foliar spray recorded significantly maximum plant height (42.87 cm), plant spread (61.34 cm), number of leaves (31.17), MSI of the petal tissue (84.55, 79.77 and 75.50 %), maximum yield per plant (57.17) and vase life of the flower (9.29 days) which was followed by the treatment combination of bio fertilizers along with foliar spray of 4% vermiwash. Higher chlorophyll content in leaf tissue (2.03 mg/g) and lignin content in the flower stalk (6.84 %) were found with the treatment combination of bio fertilizers along with 4% vermiwash foliar spray which was at par with bio fertilizers along with 25 ppm spermine. Thus, the treatment combinations of bio fertilizers along with foliar spray of 25 ppm spermine or 4% vermiwash significantly improved the growth, yield and vase life of gerbera.